Development of high-quality hexahedral human brain meshes using feature-based multi-block approach - Mao, Haojie; Gao, Haitao; Cao, Libo; Genthikatti, Vinay Veeranna; Yang, King H. (Computer methods in biomechanics and biomedical engineering, 2013)
The finite element (FE) method is a powerful tool to study brain injury that remains to be a critical health concern. Subject/patient-specific FE brain models have the potential to accurately predict a specific subject/patient's brain responses during computer-assisted surgery or to design subject-specific helmets to prevent brain injury. Unfortunately, efforts required in the development of high-quality hexahedral FE meshes for brain, which consists of complex intracranial surfaces and varying internal structures, are daunting. Using multi-block techniques, an efficient meshing process to develop all-hexahedral FE brain models for an adult and a paediatric brain (3-year old) was demonstrated in this study. Furthermore, the mesh densities could be adjusted at ease using block techniques. Such an advantage can facilitate a mesh convergence study and allows more freedom for choosing an appropriate brain mesh density by balancing available computation power and prediction accuracy. The multi-block meshing approach is recommended to efficiently develop 3D all-hexahedral high-quality models in biomedical community to enhance the acceptance and application of numerical simulations.